If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-2(3x-2)=-2
We simplify the equation to the form, which is simple to understand
x-2(3x-2)=-2
Reorder the terms in parentheses
x+(-6x+4)=-2
Remove unnecessary parentheses
+x-6x+4=-2
We move all terms containing x to the left and all other terms to the right.
+1x-6x=-2-4
We simplify left and right side of the equation.
-5x=-6
We divide both sides of the equation by -5 to get x.
x=1.2
| 4a-3a+4b+2+3= | | 5(2+3p)=-8 | | 4a+2b-10+3b= | | 4x-2=4(x-2) | | 9x+2y-3x+5-3= | | -4=6+x | | 4a-8=2a-2 | | 27=7(2y+1) | | 4.5f=3.6 | | 16x^2+1-8x=0 | | g+2.7=27 | | 15.5a=-25.5 | | 88-25=61/11(h-5) | | 5+3(x+2)=12 | | y-23.9=18.5 | | 4(x+6)=3x | | 3(3x-2)=-51 | | 37.7+m=53.9 | | 0.33-b=-0.99 | | 3h=4(h+6) | | 22x+12x=60 | | 0.133-but=-0.99 | | 88-30=27/4(h-5) | | (4x+2)+(7x+7)+5x-4= | | p-88-30=27/4(h-5) | | p-30=27/4(20-5) | | p-30=27/4(18-5) | | 4000(1+0.041/4)4t=0 | | -5(x-5)+7x=4x-4 | | 11=9(1+2p) | | 6x+18=12x | | 15x-7=27x+1 |